Population Based Electronic Surveillance Tool to Identify Risk Factors for Developing Cervical Cancer- A Study Protocol - CNV SAI Bharath; Gupta, Satish Kumar; KM Monirul Islam; Joshi, Ashish; Verma, Garima; Verma, Anjana; Akthar, Nadeem (National Journal of Community Medicine, 2024)
Background: Cervical cancer remains a significant global health concern, with well-established risk factors. Population-based electronic surveillance tools offer a promising avenue for identifying risk factors associated with cervical cancer development way before it becomes an actual concern for a woman. The objective of this study is to understand and to support the app- based decision-making tool for identifying risk factors of cervical cancer for the women between 30-60 years of age. Method: The study will be conducted in the selected Sampoorna Non-Communicable Diseases (NCD) clinics at Lucknow, Uttar Pradesh (UP). A rigorous review of database was conducted to summarize the evidence on informatics available for early identification of cervical cancer app. An app-based decision- making tool will be developed to identify and detect the high- risk population developing cervical cancer. The app then will be shared with health workers at Sampoorna clinics and will be capacitated for using it to collect real time data. Conclusion: The utilization of a population-based electronic surveillance tool will facilitate the identification of various risk factors contributing to cervical cancer development. The methodology process will help to comprehend the analysis providing the insights. This approach has the potential to enhance targeted interventions, public health policies, and personalized screening programs to mitigate the burden of cervical cancer. The objective of this paper is to understand and to support the design of dashboards for creating transparency and accountability.